Change in Skin Temperature, Stratum Corneum Water Content and Transepidermal Water Loss During Cycling Exercise (Journal of Fiber Bioengineering and Informatics, 2013)
The study investigated the skin temperature (T_{sk}) at sixteen points, Stratum Corneum Water Content(SCWC) and TransepidermalWater Loss (TEWL) at fourteen points over the ventral and dorsal surfaces,during submaximal cycling exercise in an ambient temperature of 25 °C, and a relative humidity of 60%.Nine healthy competitive males completed a 20 min rest on the cycle and 5-min warm-up, followed bya 30 min of cycle exercise at 70% maximal heart rate and 30 min recovery. Average mechanical poweroutput and pedaling rate were 150 W and 70 rpm. The results showed that the ventral and dorsal skintemperatures were significantly decreased from a minimum of 0.68 °C up to 3.48 °C than those measuredat rest before cycling. In accordance with the regions of declines in skin temperatures, the values ofSCWC and TEWL almost attained 120 A.C.U. and 40 ∼ 60 g ⁄ h.m². Meanwhile, the subjects produced0.45 L ⁄ h sweating throughout the experiment. The distribution state of Tsk, SCWC and TEWL couldbe visualized directly by a novel color mapping of human body. The results obtained suggest thatduring the submaximal cycling exercise, the reduction of skin surface temperature is associated with theevaporative heat loss due to skin sweat.
Keywords: Skin Temperature; Stratum Corneum Water Content; Transepidermal Water Loss; Skin Sweat; Cycle Exercise